Peran Dinas Pariwisata Dalam Meningkatkan City Branding Pada Promosi Wisata Kabupaten Aceh Selatan - Sri Maulida; Fazri, Anhar (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
South Aceh Regency, Aceh Province is one area that has a variety of tourist destinations, both marine tourism, mountains, water, culture, religion and a number of other destinations. One of the efforts to improve the image of a tourist destination in an area is through city branding, namely the strategy of a region in making a strong positioning towards their market, in this case tourists, such as positioning a product or service, so that the city can be widely known by the public. . However, the concept of city branding carried out by the South Aceh Tourism Office (Dispar) has not been analyzed sharply and in depth as an illustration and benchmark for tourism promotion in the district. Based on the results of the research that has been carried out, it can be concluded that mapping surveys, competitive analysis, blueprints and implementation are important for building city branding in South Aceh